A Practical Framework for Integrating Advances in Ergonomics to Improve Productivity in South African Small and Medium Enterprises - Mukalay, T. A.; Swanepoel, J.; Nenzhelele, T. (The South African Journal of Industrial Engineering, 2025)
This study provides a practical framework for integrating advances in ergonomics into South African small and medium enterprises to enhance productivity. Informed by a comprehensive literature review and insights from the 2025 Applied Ergonomics Conference, the proposed three-phase framework comprises an ergonomics intervention trigger checklist and related productivity metrics; an integration matrix aligned with ISO 45001:2018 and ISO TR 12295:2014; and strategies to overcome adoption barriers. The framework incorporates participatory design, simplified assessment tools, and interventions such as wearable technologies. By addressing a gap in the research, this study offers a scalable, cost-effective framework that is tailored to the resource-constrained small and medium enterprises’ environment.